2009
DOI: 10.2135/cropsci2008.04.0221
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Effects on Seed Germination and Vegetative Growth of Greens‐Type Poa annua Relative to Other Cool‐Season Turfgrass Species

Abstract: Seed germination and vegetative growth studies were conducted to determine relative salinity tolerance of greens‐type Poa annua L. compared with other cool‐season turfgrass species. Effects of increasing salinity stress on final germination percentage (FGP), germination rate (GR), clipping yield dry weight (CYD), verdure dry weight (VD), root dry weight (RD), and the longest root length (LRL) were evaluated for nine experimental lines of greens‐type P. annua, two cultivars of Kentucky bluegrass (P. pratensis L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
33
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 21 publications
9
33
1
1
Order By: Relevance
“…89%) demonstrating salt tolerance in the period of seed germination. It is in agreement with the previous study of Dai et al (2009), who stated that L. perenne was relatively the most salt-tolerant among the tested several cool-season turfgrass species. Our results have been confirmed in the studies by Kusvuran et al (2015), who found that salt stress caused 17% reductions in germination in the turfgrass varieties of L. perenne with the 200 mM NaCl treatment.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…89%) demonstrating salt tolerance in the period of seed germination. It is in agreement with the previous study of Dai et al (2009), who stated that L. perenne was relatively the most salt-tolerant among the tested several cool-season turfgrass species. Our results have been confirmed in the studies by Kusvuran et al (2015), who found that salt stress caused 17% reductions in germination in the turfgrass varieties of L. perenne with the 200 mM NaCl treatment.…”
Section: Resultssupporting
confidence: 93%
“…The seeds at germination are most susceptible to salinity stress and studies in this field indicate considerable differentiation of grass seeds within the species and varieties in tolerating salinity (Hujun et al, 2001;Jalali et al, 2010). According to Dai et al (2009), the germination of several cool-season turfgrass species showed L. perenne to be relatively the most salt-tolerant while P. pratensis the least. However, the existing results do not give complete information on this subject.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…seeds on different salinity levels. Dai et al (2009) also compared salinity tolerance of greens-type P. annua. Germination rate and seedling growth (blade length and tissue weight) of perennial ryegrass, kentucky bluegrass, and tall fescue cultivars under saline conditions were evaluated in hydroponic systems (Horst and Beadle, 1984;Horst and Dunning, 1989;Horst and Taylor, 1983).…”
Section: Introductionmentioning
confidence: 99%